Interaksi Lingkungan dan Psikologi Perkembangan dalam Pembentukan Karakter Peserta Didik - Wulandari Berliana Sapyudin; Ellen Prima (Indo Publishing, 2026)
The interaction between environmental factors and psychological development plays a significant role in shaping students' character. Family, school, community, and digital environments serve as primary settings where students gain social, emotional, and educational experiences that influence their personal growth. At the same time, psychological development, which includes cognitive, emotional, social, and moral dimensions, affects how students interpret, respond to, and internalize values obtained from their surroundings. This article aims to examine the relationship between environmental influences and psychological development in the process of character formation among students, as well as to highlight the importance of collaboration among various educational stakeholders. The study employs a library research method by reviewing and analyzing relevant literature related to educational environments, developmental psychology, and character education. The findings indicate that supportive and positive environments contribute to healthy psychological growth and encourage the development of desirable character traits, such as responsibility, discipline, honesty, social awareness, and adaptability. Conversely, unfavorable environments may hinder both psychological development and character formation. Therefore, cooperation among families, schools, and communities is essential to create conditions that support students' holistic development and character building.